Modernising meat inspection using risk-based approaches - Alban, L.; Albuquerque, E.R.; Capobianco-Dondona, A.; Kautto, A.H.; Klottrup, A.; Meemken, D.; Oorburg, D.; Poulsen, M.K.; Grace, Delia; Vieira-Pinto, M.; Blagojevic, B. (2024)
A workshop at the SafePork Conference in 2023 delved deeply into the concepts and practicalities of risk-based meat inspection. Such approaches could significantly improve food safety while making the process more efficient and cost-effective.